What is important to service users and staff when implementing suicide-focused psychological therapies for people with psychosis into mental health services? - Peters, Sarah; Awenat, Yvonne; Gooding, Patricia A.; Harris, Kamelia; Cook, Leanne; Huggett, Charlotte; Jones, Steven; Lobban, Fiona; Pratt, Daniel; Haddock, Gillian (Frontiers in Psychiatry, 2023)
Suicide is a leading cause of death globally. People with psychosis are at increased risk of suicide death and up to half experience suicidal thoughts and/or engage in suicidal behaviours in their lifetime. Talking therapies can be effective in alleviating suicidal experiences. However, research is yet to be translated into practice, demonstrating a gap in service provision. The barriers and facilitators in therapy implementation require a thorough investigation including the perspectives of different stakeholders such as service users and mental health professionals. This study aimed to investigate stakeholders’ (health professionals and service users) perspectives of implementing a suicide-focused psychological therapy for people experiencing psychosis in mental health services. Face-to-face, semi-structured interviews with 20 healthcare professionals and 18 service users were conducted. Interviews were audio recorded and transcribed verbatim. Data were analysed and managed using reflexive thematic analysis and NVivo software. Participants valued a therapy that focuses on suicidal experiences. A key finding was that all stakeholders viewed a suicide-focused therapy as valuable for people experiencing psychosis. For this type of therapy to be successfully implemented in services, there are four key aspects that need to be considered: i. Creating safe spaces to be understood; ii. Gaining a voice; iii. Accessing therapy at the right time; and iv. Ensuring a straightforward pathway to accessing therapy.